Challenges Facing the Elderly in Tanzania (Tanzania Journal for Population studies and Development, 2011)
This article assesses livelihood challenges facing the elderly in urban and rural settings in Tanzania. It is based on a study conducted in Morogoro Urban and Mvomero Districts in Morogoro Region in 2011. The study was based on the assumption that with the seemingly disintegrating traditional extended families and social support systems, the elderly are increasingly facing more livelihood challenges. The article examines the effect of ageing on the livelihood activities of the elderly in rural and urban areas, and identified the challenges they face. The data for the study was collected from 162 elderly people aged 60 years and above. It was found out that the majority of the elderly in the study area had no formal education, and with ageing, there has been a significant shift in their occupations. The very old are unable to work. The overall situation of vulnerability to poverty is critical in the rural areas. It is argued that the elderly face the following challenges: lack financial support; accessibility to health facilities; lack of respect and property security, and loneliness. The article concludes that the elderly are in a desperate livelihoods situation. It recommends that effective strategies be formulated in implementing the national ageing policy that was formulated in 2003. More important, there is the need to consider the possibility of an ageing pension to all elderly people in the country which, according to HelpAge International (2011), is within the capacity of the government of Tanzania.